Pendidikan Keluarga sebagai Fondasi Regenerasi Pengukir Muda di Desa Mulyoharjo, Jepara - Aghnia, Innaz Muthia; Eko Haryanto; Muh Fakhrihun Naam (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Family education is the main foundation in shaping the next generation to have strong character, high morality, and creativity to become accomplished young achievers. Through guidance and example from parents, noble values, ethics, and a fighting spirit are instilled from an early age, making them individuals ready to face the challenges of the times. Thus, the role of the family is not limited to education but also to fostering the regeneration of young carvers. The study was conducted to examine the role of family education in preserving and regenerating woodcarving art in Mulyoharjo Village, Jepara. The research used a qualitative approach, with data presented descriptively through interviews, observations, and documentation. The results of the research indicate that informal education within the family environment serves as the primary foundation for shaping the character, work ethic, and technical skills of young woodcarvers. From a young age, children are directly exposed to woodcarving activities, learning indirectly from their parents or other family members. The learning process not only involves the transfer of techniques but also instills noble values such as perseverance, precision, and a love for tradition. The role of parents as mentors and facilitators is crucial in nurturing children's interests and talents. It can be concluded that family education is the key to the sustainability of woodcarving art in Mulyoharjo Village. As such, support from various parties, including village governments and communities, is needed to strengthen the role of families as centers of cultural inheritance.